2011
DOI: 10.1158/1078-0432.ccr-10-2533
|View full text |Cite
|
Sign up to set email alerts
|

HOXB7 as a Prognostic Factor and Mediator of Colorectal Cancer Progression

Abstract: Purpose: This study was to investigate the clinicopathologic significance and potential role of HOXB7 in the development and progression of colorectal cancer (CRC).Experimental Design: The relationship between HOXB7 expression and clinical characteristics of CRC was analyzed in 224 paraffin-embedded archived CRC specimens by immunohistochemistry (IHC). The effects of HOXB7 on cell growth and proliferation, as well as on tumorigenesis, were examined both in vitro and in vivo, using MTT assay, colony formation a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
170
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(188 citation statements)
references
References 35 publications
(50 reference statements)
15
170
0
3
Order By: Relevance
“…BUB1B [budding uninhibited by benzimidazones 1 homolog beta (yeast)] encodes a kinase involved in spindle checkpoint function and plays a role in the inhibition of anaphase-promoting complex/cyclosome, delaying the onset of anaphase and ensuring proper chromosome segregation (Davenport et al, 1999), over expression of BUB1B is significantly correlation with a less advanced pathologic stage in oral squamous cell carcinoma (Rizzardi et al, 2011). HOXB7 (homeobox protein Hox-B7) is a member of the Antp homeobox family, which functions as a sequence-specific transcription factor involved in cell proliferation and differentiation (McAlpine and Shows, 1990), over expression of HOXB7 is significantly correlate with advance stage and poor prognosis of colorectal cancer (Liao et al, 2011) and oral squamous cell carcinoma (Bitu et al, 2012), TOP2A (DNA topoisomerase II-alpha) encodes an enzyme that controls and alters the topologic state of DNA during transcription (Watt and Hickson, 1994), over expression of TOP2A is associated with better overall survival and disease-free survival in early breast cancer treated with anthracyclines (Arriola et al, 2007). The association of these genes expression with the clinical features of cholangiocarcinoma are worthy further studied due to these information have not been reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…BUB1B [budding uninhibited by benzimidazones 1 homolog beta (yeast)] encodes a kinase involved in spindle checkpoint function and plays a role in the inhibition of anaphase-promoting complex/cyclosome, delaying the onset of anaphase and ensuring proper chromosome segregation (Davenport et al, 1999), over expression of BUB1B is significantly correlation with a less advanced pathologic stage in oral squamous cell carcinoma (Rizzardi et al, 2011). HOXB7 (homeobox protein Hox-B7) is a member of the Antp homeobox family, which functions as a sequence-specific transcription factor involved in cell proliferation and differentiation (McAlpine and Shows, 1990), over expression of HOXB7 is significantly correlate with advance stage and poor prognosis of colorectal cancer (Liao et al, 2011) and oral squamous cell carcinoma (Bitu et al, 2012), TOP2A (DNA topoisomerase II-alpha) encodes an enzyme that controls and alters the topologic state of DNA during transcription (Watt and Hickson, 1994), over expression of TOP2A is associated with better overall survival and disease-free survival in early breast cancer treated with anthracyclines (Arriola et al, 2007). The association of these genes expression with the clinical features of cholangiocarcinoma are worthy further studied due to these information have not been reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…The relative miR-224 expression levels after normalization to U6 small nuclear RNA were calculated using 2 À[(Ct of miR-224) À (Ct of U6)] . Realtime quantitative PCR for target genes was conducted as previously described (13). Primer sequences were summarized in Supplementary Table S1.…”
Section: Tissue Specimens and Cell Culturesmentioning
confidence: 99%
“…The MTT assay, colony formation assay, soft-agar colony formation assay, flow cytometry, and immunohistochemistry (IHC) were conducted according to previously described methods (13). Further details are provided in the Supplementary Materials and Methods section.…”
Section: Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…HOXB7 was also found deregulated in myeloma (Novak et al, 2010), lung cancer (Yuan et al, 2014), oral squamous cell cancer (Xie et al, 2013) and many other types of cancer (Srebrow et al, 1998;Liao et al, 2011;Nguyen Kovochich et al, 2013;Braig et al, 2010). Moreover, overexpression of HOXB7 was associated with poor prognosis of breast cancer (Srebrow et al, 1998), colorectal cancer (Liao et al, 2011) and oral squamous cell cancer (Xie et al, 2013). Molecular and biochemical studies indicated that HOXB7 could promote proliferation of esophageal cancer cells (Xie et al, 2013), interact with proteins about DNA repair (Rubin et al, 2007), promote transforming ability in human breast epithelial cells (Srebrow et al, 1998).…”
Section: Hoxb7 Predicts Poor Clinical Outcome In Patients With Advancmentioning
confidence: 99%